A fiscal approach to the social contract in subSaharan African countries: Looking for opportunities to strengthen trust in government and tax compliance by analysing citizens' perception of governance - Enrico Nichelatti; Heikki Hiilamo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The COVID-19 pandemic showed that many developing countries could not respond effectively to crises due to their limited capacity to diversify their social protection responses. Social protection systems depend mainly on government tax revenue capacity. Raising domestic revenue still represents a priority for most sub-Saharan African countries, which continue to face high tax non-compliance. This research investigates whether there is a link between citizens' perceptions of governance and individual tax compliance in sub-Saharan Africa. We employ a logistic regression model and use Round 7 of the Afrobarometer, whichcontains information on Africans' views on democracy, governance, economic reform, civil society, and quality of life for 32 countries. Furthermore, in addition to a regression analysis, the study proposes a binary mediation analysis to investigate the direct and indirect effects of governance perception on individual tax compliance, with trust in institutions serving as a mediator. The main results suggest that perceptions of governance and attitudes towards tax compliance are positively associated, and their impact differs by country.
Keywords: C21; C25; H26; Z18; 330; tax compliance; perception of governance; sub-Saharan Africa; tax revenue; regression analysis; binary mediation analysis